Plastic Pollution, Climate Change, and the Moral Imperative to Respond - Schwartz, Andrew (Theology and science, 2025)
Plastics have profoundly reshaped our global environment. Once hailed as a miracle invention, they now represent both a tangible and existential threat to life on Earth. This essay draws parallels between plastic pollution and the concept of structural sin, framing plastics as not only a material crisis but also a moral one. In response, Christians must move beyond passive belief toward active resistance—challenging systems of environmental degradation and systemic injustice, and demanding collective accountability.